Triage imaging and outcome measures for large core stroke thrombectomy – a systematic review and meta-analysis. (26th May 2020) - Sarraj, Amrou; Grotta, James C; Pujara, Deep Kiritbhai; Shaker, Faris; Tsivgoulis, Georgios
Abstract : Background: Trials of endovascular thrombectomy (EVT) mostly excluded patients with large core strokes so the safety and efficacy of EVT is not well established in such patients. Moreover, the definition of large core and its measurement differ between semi-quantitative (ASPECTS) and quantitative (core volume) imaging modalities. We evaluated functional and safety outcomes in studies reporting large core stroke patients treated with EVT and compared them with patients treated with medical management (MM) only. Methods: A systemic search using three large databases was performed to identify studies evaluating functional and safety outcomes in patients with large core strokes (ASPECTS<6 or core volume ≥50 cc) on CT, MRI, and Perfusion imaging according to PRISMA guidelines. A random-effect meta-analysis model was used to pool reported outcomes. Results: Twelve studies reporting outcomes for patients treated with EVT compared with MM in large core strokes were included. A pooled random-effect meta-analysis of large core patients by either definition (ASPECTS <6 or ischemic core volume ≥50 cc or both) demonstrated increased functional independence (mRS-scores 0–2) rates with EVT (EVT: 122/491 (25%), MM: 45/691 (7%), pooled OR: 4.39 [95% CI: 2.53 to 7.64], overall effect Z-score: 5.25, P<0.00001, I 2 =37%, P for Cochran Q:0.15) and decreased mortality (EVT: 101/439 (23%), MM: 215/645 (33%), pooled OR:0.53 [95% CI: 0.40 to 0.71], overall effect Z-score:4.32, P<0.0001, I 2 =0%, P for Cochran Q:0.78) at 90 days, without significant increase in symptomatic intracranial hemorrhage (ICH) (EVT: 42/462 (9%), MM: 35/663 (5%), pooled OR: 1.68 [95% CI: 0.92 to 3.09], overall effect Z-score:1.68, P=0.09, I 2 =26%, P for Cochran Q:0.24). Similar effects were observed in studies reporting large core outcomes based on ASPECTS <6 and ischemic core volume ≥50 cc. We observed no heterogeneity between quantitative vs semi-quantitative large core definitions, different ischemic core thresholds, and studies reporting outcomes over different time windows in subgroup analyses. Conclusion: In large core stroke patients, EVT is associated with improved functional independence and lower mortality at 90 days without significant increase in symptomatic ICH across various definitions, thresholds of large core size, and time windows. Further randomized evidence is warranted to establish EVT efficacy and safety in this population.